Integrando processos ambientais e espaciais na ecologia de comunidades aquáticas em escala regional - Barros, Tadeu de Siqueira (Universidade Federal de São Carlos, 2010)
For decades the search for determinants of biodiversity and structuring processes of natural communities has been concentrated on the role of environmental factors and differences in species niche. The neutral theory of biodiversity challenged this view by assuming functional equivalence between species and a major role of stochastic spatial processes. In this thesis, I aimed at analyzing how local and regional ecological processes interact to influence the structure of aquatic metacommunities. The thesis has three chapters. In the first one, I investigated one of the most widespread patterns in ecology, the relationship between species local abundance and regional distribution. I used niche characteristics, estimated independently from local and landscape metrics, to explain the relationship. In the second chapter, I tested whether common and rare species are influenced by environmental and spatial processes in a different manner. In the last chapter, I tried to identify taxon association within the Chironomidae that occur in São Paulo State. Besides, I built ecological models considering information from environmental and spatial processes at different scales aiming at predicting theses associations. In general, I conclude that to understand the dynamics of aquatic metacommunities one must include local, landscape and spatial variables in the analyses. Furthermore, it seems that some species do not differ in their realized niches. In other words, they occupy parts of the environmental gradient in a similar way, thus they respond in a similar way to the same type of ecological processes. This opens an avenue for monitoring and conservation programs. For example, we can use a reduced number of species to monitor entire communities. In my opinion, now we need to advance the way we measure and include spatial processes like dispersal in our models.
Keywords: Ecologia; Metacomunidades; Nicho (Ecologia); Teoria neutra; Dispersão; Insetos aquáticos; CIENCIAS BIOLOGICAS::ECOLOGIA